Advancing patient care: unleashing the potential of artificial intelligence in orthopaedics - Ganesh, Arjun; Mohan Kumar, M. (International Journal of Research in Orthopaedics, 2023)
I am writing to highlight the remarkable strides that artificial intelligence (AI) has taken in the field of orthopaedics, paving the way for transformative changes in patient care and clinical outcomes. As the realm of medical science evolves, integrating AI into orthopaedics has the potential to revolutionize diagnosis, treatment, and management strategies, enhancing both the precision and efficiency of orthopaedic care.